Genetic testing for familial hyperparathyroidism: clinical-genetic profile in a Mediterranean cohort - Mazarico-Altisent, Isabel; Capel, Ismael; Baena, Neus; Bella-Cueto, Maria Rosa; Barcons, Santi; Guirao, Xavier; Pareja, Rocío; Muntean, Andreea; Arsentales, Valeria; Caixàs, Assumpta; Rigla, Mercedes (Frontiers in Endocrinology, 2023)
Background: Approximately 10% of primary hyperparathyroidism cases are hereditary, due to germline 45 mutations in certain genes. Although clinically relevant, a systematized genetic diagnosis is missing due to 46 a lack of firm evidence regarding individuals to test and which genes to evaluate. Methods: A customized 47 gene panel (AIP, AP2S1, CASR, CDC73, CDKN1A, CDKN1B, CDKN2B, CDKN2C, GCM2, GNA11, 48 MEN1, PTH, RET, and TRPV6) was performed in 40 patients from the Mediterranean area with suspected 49 familial hyperparathyroidism (≤45 years of age, family history, high-risk histology, associated tumor, 50 multiglandular disease, or recurrent hyperparathyroidism). We aimed to determine the prevalence of 51 germline variants in these patients, to clinically characterize the probands and their relatives, and to compare 52 disease severity in carriers versus those with a negative genetic test. Results: Germline variants were 53 observed in 9/40 patients (22.5%): 2 previously unknown pathogenic/likely pathogenic variants of 54 CDKN1B (related to MEN4), 1 novel variant of uncertain significance of CDKN2C, 4 variants of CASR (3 55 pathogenic/likely pathogenic variants and 1 variant of uncertain significance), and 2 novel variants of 56 uncertain significance of TRPV6. Familial segregation studies allowed diagnosis and early treatment of 57 PHPT in first-degree relatives of probands. Conclusion: The observed prevalence of germline variants in 58 the Mediterranean cohort under study was remarkable and slightly higher than that seen in other 59 populations. Genetic screening for suspected familial hyperparathyroidism allows the early diagnosis and 60 treatment of PHPT and other related comorbidities. We recommend genetic testing for patients with 61 primary hyperparathyroidism who present with high-risk features.